Relationship of body fat and body mass index in young Pacific Islanders: a cross‐sectional study in European, Melanesian and Polynesian groups. Issue 6 (28th July 2017) - Frayon, S.; Cherrier, S.; Cavaloc, Y.; Wattelez, G.; Lerrant, Y.; Galy, O.
Summary: Background: Body mass index is the most often used indicator of obesity but does not distinguish between lean and fat mass. Adiposity at the same body mass index differs across ethnic groups. Objectives: The twofold aim of this study was to determine whether body mass index (BMI)‐based references are correlated with body fat percentage (%BF) in a pluri‐ethnic population of Pacific Islanders and to assess the diagnostic accuracy of these references by using the percentage of body fat as the gold standard. Methods: Height and weight were obtained, and triceps and subscapular skinfold thicknesses were measured in a sample of 796 adolescents (11–16 years) from the three main ethnic groups in New Caledonia: Melanesian, European and Polynesian. %BF was derived from the Slaughter equations, and BMI z score was calculated by using various international and national references. Results: Melanesian teens had lower %BF compared with their European counterparts for the same BMI z score. Whatever the BMI‐based reference used to detect overfatness (%BF >25% for boys and >30% for girls), sensitivity was higher in Melanesian adolescents, while specificity was higher in their European counterparts. Diagnostic accuracy was better in Melanesian compared with European adolescents. Conclusions: This study shows that Melanesian adolescents have lower %BF than their European counterparts for the same BMI z score. Therefore, the diagnostic accuracy of BMI to detect overfatness is related to ethnicity. Whatever the BMI‐based reference, sensitivity was higher in the Melanesian group, while specificity was higher in the European group.